Relevansi Myers-Briggs Type Indicator (MBTI) bagi Mahasiswa: Studi Literatur - Amathul Zeehan; Zahra Meylani Utami; Asila Rafia Rafsa; Sri Mulyeni (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
The Myers-Briggs Type Indicator (MBTI) is one of the personality assessment tools that is often used to identify individual psychological tendencies, including in the context of higher education. In the student environment, MBTI is widely used as a means of self-introduction, adjustment of learning styles, increasing the effectiveness of group work, and career planning. This article aims to examine the relevance of the application of MBTI among students using a literature study approach. The research method used is in the form of a review of various literature sources, such as scientific journals, books, and academic articles that discuss the basic concept of MBTI, its implementation in the field of education, and critical views regarding its limitations. The results of the study show that MBTI has a fairly relevant role as a non-diagnostic instrument in helping students understand their potential, learning preferences, and social and academic interaction patterns. In addition, the appropriate use of MBTI can support improved learning quality, teamwork effectiveness, and academic counseling services. However, a number of literature highlights the limitations of MBTI, especially regarding aspects of validity and reliability, so it is not recommended to be used as the sole basis for academic or psychological decision-making. Thus, MBTI remains relevant for students if used wisely, contextually, and based on a strong scientific foundation to support students' academic and personality development.